Outside offers and bidding costs - Gábor Virág (Hungarian Academy of Sciences, Institute of Economics, 2006)
This paper provides a search theoretic model with endogenous job creation, and homogenous workers and firms. The model introduces bidding costs and allows the current employer to make a counteroffer with probability q when the worker receives an outside offer. In equilibrium, a higher level of ex-post competition (q) reduces the probability that an employed worker receives an outside offer. Therefore, a higher level of ex-post competition may decrease the expected income of the workers. In the extreme case when the competition is cutthroat (q = 1), no employed worker receives outside offers and each employed worker earns only the minimum wage. In contrast to existing models, our model allows for wage dispersion even if all frictions (including bidding and search costs) converge to zero simultaneously. When bidding costs are small and ex-post competition is strong, a small change in parameter values may influence the equilibrium bidding, wage distribution and job creation substantially. Consequently, it is not only the overall level of market frictions that matters, but also their structure.
Keywords: C78; D83; J64; 330; counteroffers; wage dispersion; job creation; Personalbeschaffung; Lohnstruktur; Arbeitsmarkt; Suchtheorie; Theorie